Effect of Aging on the Lower Limb Kinematics in Karate Practitioners: Comparing Athletes and Their Senseis - Branco, Marco A. C. (2019)
With the life expectancy increasing, older adult population has gained the attention of many researchers. Aging is known to lead to a general decline in bodily functions, which affect the quality of life. The aim of this study was to analyze how the aging process affects veteran active karate practitioners, in the kinematic and temporal structure of the frontal kick. Nine black belt karate practitioners over 50 years old and 24 black belt karate practitioners, aged between 20 and 30 years old, all male, performed the frontal kick mae-geri. Results showed that knee is the structure that holds most differences between young and veterans, both for linear and for angular variables during the mae-geri performance. Statistical differences were found in linear velocity for the knee; linear acceleration of the knee, hip, and RASIS; maximum angular velocity for knee and hip; maximum angular acceleration for ankle and hip; and in the range of motion of knee. The temporal variables show differences, between groups, in maximum linear velocity, maximum linear acceleration, and maximum angular acceleration. However, no differences were found between groups for the time before contact in the maximum linear and angular acceleration, which allow us to remark both the effects of the aging process and the effect of training. This study corroborates the ability of older people to achieve benefits from sports practice, achieving higher efficiency than the younger adults in task execution, but using different motor control strategies.